Splendors and Miseries of Administrative Justice in Cameroon (African Journal of Law and Politics, 2025)
What are the main advances and limitations that apply to the new administrative jurisdiction in Cameroon? The question is serious. The question indeed deserves to be observed with great consideration and only a careful examination of the legal standards in force as well as court decisions would make it possible to judge it. The time has undoubtedly arrived today, after the effective implementation of the newly created Administrative Tribunals, to note the main positive and negative aspects of the latest treatment chosen by the legislator and, as far as possible, to predict the chances of healing of Cameroonian administrative disputes. Thus, we intend to demonstrate throughout the following developments that administrative litigation has experienced sawtooth developments in Cameroon with advances here, and regressions there. From 1996 to today, developments should nevertheless be noted in Cameroonian administrative litigation. Administrative jurisdiction has truly been transformed. The 2006 reform which saw the creation of administrative courts and the reorganization of the Administrative Bench of the Supreme Court aimed to promote administrative litigation which remains weak in both qualitative and quantitative terms. In the end, the changes are slight since the organizational principles, in particular, remain the same. The lack of audacity noted in the new organic structuring of the administrative jurisdiction is an incongruity which cannot go unnoticed. The system remains incomplete and the absence of a sovereign court reserved for administrative functions, separate from other functions, particularly judicial ones, maintains the Cameroonian model in a typically African uniqueness and disinclined to efficiency. Only a firm option for the emergence of a true administrative judge, technically competent, would have been a guarantee of a satisfactory distribution of the justice in question.